1997
DOI: 10.1002/(sici)1097-4628(19970516)64:7<1291::aid-app7>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ?-irradiation dose for the oxygen diffusion into polymers

Abstract: Electron spin resonance (ESR) spectroscopy has been used for the measurement of the diffusion coefficient of oxygen into polymeric spheres. It has been shown that there is an inverse dependency between the irradiation dose and the oxygen diffusion coefficient (D). The free-radical concentration (R 0 ) produced in the polymer depends on the dose of the g rays. In this study, we tried to find a relationship between the oxygen diffusion coefficient and the free-radical concentration produced in the polymer during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…When vacuum-irradiated polymers are exposed to air, the radicals trapped in the material are transformed into peroxide radicals by the addition of molecular oxygen to the free radicals. Kaptan and Guven [69] have irradiated PMMA with γ radiation in a vacuum and reported a nine-line ESR spectrum. They also showed that the nine-line spectrum changed to a single-peak spectrum when exposed to air, due to the formation of an antisymmetric peroxide radical.…”
Section: Resultsmentioning
confidence: 99%
“…When vacuum-irradiated polymers are exposed to air, the radicals trapped in the material are transformed into peroxide radicals by the addition of molecular oxygen to the free radicals. Kaptan and Guven [69] have irradiated PMMA with γ radiation in a vacuum and reported a nine-line ESR spectrum. They also showed that the nine-line spectrum changed to a single-peak spectrum when exposed to air, due to the formation of an antisymmetric peroxide radical.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum temperature where the reliable measurements were carried out was 50°C for PVAc irradiated to a 15-kGy dose. 11 The ln D versus inverse temperature plot is represented by a single line for PMMA. The same plot, however, shows a break at 35°C for PVAc.…”
Section: Resultsmentioning
confidence: 99%
“…The initiation of oxidation in the phenolic resins containing metallic oxides is fulfilled by superficial adsorption, when the free radicals may be easily converted due to the initial amounts of gaseous oxygen initially existing in the organic phase [22]. However, the catalytic auto-oxidation process is sustained either by the interaction between the filler and resin, or by the propagation of the oxidation chain [23].…”
Section: Discussionmentioning
confidence: 99%